Does Internet Usage Stimulate the Accumulation of Social Capital? A Panel Investigation for OECD Countries - Salahuddin, Mohammad; Alam, Khorshed; Burton, Lorelle (International Journal of Economics and Financial Issues, 2016)
This study estimates the effects of the Internet and economic growth on the accumulation of social capital (measured by trust) using panel data for 19 OECD countries for the period 1985-2012. A cross sectional dependence (CD) test is performed. Having found the cross sectional dependence, a cross-sectionally augmented IPS (CIPS) unit root test is conducted to check for stationarity of data. All the variables were found first-difference stationary. Pedroni cointegration test confirms the presence of long-run relationship among the variables. This follows the application of Pooled Mean Group regression (PMG) technique to estimate the short- and long-run association between the variables. The findings suggest a highly significant negative long- run relationship between Internet usage and social capital and a positive relationship between them in the short-run. However, both long-run and short-run coefficients are small in magnitude. Economic growth stimulates social capital both in the short- and the long-run. That the Internet reduces social capital in the long-run implies that the gains in trust obtained from online connectivity were perhaps offset by the loss in the same due to decline in frequency of offline interaction caused by increasing online engagement. Economic growth stimulates activities in markets that engage into more frequent transactions between businesses that may result in increased trust. Finally, the findings of this study do not rule out the potential of including social capital issue into the digital divide policies of these countries. Keywords: Economic growth, Internet usage, OECD, panel data, social capital JEL Classifications: C23; F43; O